Cadeia global de valor: a influência da governança internacional na produção de cacau no Brasil (2015-2020) - Vieira, Wellyda de Araujo (Universidade Federal do Tocantins, 2024)
The cocoa commodity as a product with high value and export potential means that the quantity of its production alone is not enough to give characteristics to the competitiveness of international trade. From the perspective of global value chains, Brazil is considered a country that supplies raw materials, while the governance of this chain is concentrated in a developed country, where the most important part of the chain is condensed and absorbs the most expressive gains. This segment of agribusiness is noted in a comprehensive way, from the perspective of productive and commercial globalization. The production of raw materials, industrialization, and commercialization are the characteristics that command the Global Value Chain - CGV, and cocoa production has been undergoing a significant process of productive concentration and increased productivity. The objective of this work is to analyze how the governance of the global cocoa value chain influences cocoa production in Brazil. From a quantitative and qualitative analysis of data, it was possible to verify that governance manages to encourage cocoa production in Brazil through programs for the development of the cocoa production chain. It is concluded that cocoa producers in Brazil are influenced to improve their cocoa bean treatment techniques to meet the demand of international trade, based on the incentives of governance institutions of the global cocoa value chain.